PENGARUH BUDAYA UNIVERSITAS TERHADAP KINERJA MAHASISWA AKUNTANSI DENGAN KREATIVITAS SEBAGAI VARIABEL MODERASI (STUDI PADA MAHASISWA AKUNTANSI DI PERGURUAN TINGGI SE-KABUPATEN BULELENG) - Anantawikrama Tungga Atmadja; Komang Adi Kurniawan Saputra (Universitas Negeri Malang, 2018)
This research aimed to examine the influence of university culture on student performance with creativity variable as moderator. This research used survey method with questionnaire; the number of sample is 200 accounting students in North Bali, sampling technique used in this research is purposive sampling. Test of analysis used a simple regression test method and MRA (Moderated Regression Analysis). The results of this research indicate that the university culture has an effect on the performance of accounting students, and the variables of creativity moderate the influence of the university culture on student performance.Keywords:University culture; performance; creativity